Transient Hypothyroidism During Lactation Arrests Myelination in the Anterior Commissure of Rats. A Magnetic Resonance Image and Electron Microscope Study - Lucia, Federico S.; Pacheco-Torres, Jesús; González-Granero, Susana; Canals, Santiago; Obregón, María-Jesús; García-Verdugo, José M.; Berbel, Pere (Frontiers in Neuroanatomy, 2018)
Thyroid hormone deficiency at early postnatal ages affects the cytoarchitecture and function of neocortical and telencephalic limbic areas, resulting in impaired associative memory and in a wide spectrum of neurological and mental diseases. Neocortical areas send interhemispheric axons mostly through the corpus callosum and to a lesser extent through the anterior commissure (AC), while limbic areas mostly project through the AC and hippocampal commissures. Functional magnetic resonance data of children late diagnosed for congenital hypothyroidism with abnormal verbal memory processing suggest altered ipsi- and contra- lateral telencephalic connections. Gestational hypothyroidism affects AC development but the possible effect of transient and chronic postnatal hypothyroidism as occurs in late diagnosed neonates with congenital hypothyroidism and in children growing up in iodine deficient areas still remains unknown. We have studied AC development using in vivo magnetic resonance imaging and electron microscopy in hypothyroid and control male rats. Four groups of methimazole (MMI) treated rats were studied. One group was MMI-treated from postnatal day (P) 0 to P21; some of these rats were additionally treated with L-thyroxine (T4) from P15-21, as a model for early transient hypothyroidism. Other rats were MMI-treated from P0-150 and the remaining from embryonic day 10 to P170, as a chronic hypothyroidism group. The results were compared with age paired control rats. The normalized T2 signal using magnetic resonance image was higher in MMI-treated rats and correlated with the number and percentage of myelinated axons. Using electron microscopy, we observed decreased myelinated axon number and density in transient and chronic hypothyroid rats at P150, unmyelinated axon number increased slightly in chronic hypothyroid rats. In MMI-treated rats, the myelinated axon g-ratio and conduction velocity was similar to control rats, but with decreased conduction delays. These data show that early postnatal transient and chronic hypothyroidism alters AC maturation, which cannot be reverted after delayed T4-treatment. These alterations affect contralateral connections through the AC, including those between the piriform cortex and amygdaloid areas. Our data support the neurocognitive delay found in late T4-treated children with congenital hypothyroidism, and may help to understand the physiopathology of psychiatric diseases such as bipolar disorder and schizophrenia.